Analysis of Problem Based Learning Model with Mind Mapping to Increase 21st Century Skills (Journal of Innovative Science Education, 2020)
Education in the 21st Century is expected to produce human resources that have the ability to face the challenges in the development of science and technology so fast. 21st Century skills that need to be developed in students include critical thinking skills, creative thinking, collaboration, and communication. This research has purpose to determine the effectiveness of the model of Problem Based Learning (PBL) aided mind mapping to increase creative thinking skills and student collaboration. Type of research was mixed methods research design sequential exploratory. The sample of the research were 30 students of grade VIII D consisting of 16 male students and 14 female students. The analysis of the data in this research using qualitative and quantitative analysis techniques. The results showed that there is an increase in scores obtained by students in creative thinking and collaboration skills. The benefits of this research for educators are to provide effective learning model reference to be used in developing the creative thinking skills and student collaboration. Based on the result of the research, can be concluded that the PBL teaching model with mind mapping in motion and force effective to be applied in developing the creative thinking skills and student collaboration.